2020
DOI: 10.3892/mmr.2020.11298
|View full text |Cite
|
Sign up to set email alerts
|

Whole‑exome sequencing identifies a novel mutation of SLC20A2 (c.C1849T) as a possible cause of hereditary multiple exostoses in a Chinese family

Abstract: although the main causative genes for hereditary multiple exostoses (HMe) are exostosin (EXT)-1 and EXT-2, there are numerous patients with HMe without EXT-1 and EXT-2 mutations. The present study aimed to identify novel candidate genes for the development of HMe in patients without EXT-1 and EXT-2 mutations. Whole-exome sequencing was performed in a chinese family with HMe and without EXT-1 and EXT-2 mutations, followed by a combined bioinformatics pipeline including annotation and filtering processes to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Our previous study showed that the mutation of SLC20A2 (c.C1849T) was at the highly conserved amino acid sequences, at which a mutation might have a great probability to induce structural and functional changes. 10 Other studies have also reported severe Pi transport impairment in cells with SLC20A2 mutations. 30,34,35 In particular, in the study by Taglia et al 30 mentioned above, although the authors did not find significant changes in PiT-2 expression in SLC20A2 mutant cells, they observed significantly reduced Pi uptake, which may be attributed to altered PiT-2 subcellular localization in cells with the SLC20A2 mutation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our previous study showed that the mutation of SLC20A2 (c.C1849T) was at the highly conserved amino acid sequences, at which a mutation might have a great probability to induce structural and functional changes. 10 Other studies have also reported severe Pi transport impairment in cells with SLC20A2 mutations. 30,34,35 In particular, in the study by Taglia et al 30 mentioned above, although the authors did not find significant changes in PiT-2 expression in SLC20A2 mutant cells, they observed significantly reduced Pi uptake, which may be attributed to altered PiT-2 subcellular localization in cells with the SLC20A2 mutation.…”
Section: Discussionmentioning
confidence: 95%
“…The mutation of SLC20A2 (c.C1849T) was identified by whole-exome sequencing in a Chinese family with HME without EXT-1 and EXT-2 mutations. 10 The proband (age, four years; sex, male) sought medical advice at our hospital due to multiple exostoses at the bilateral distal femur, proximal tibia and fibula, distal tibia, proximal humerus, and left scapula. The mother and grandfather of the proband were also diagnosed with HME.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations